Lyric and city in “reféns da metrópoLe”, by Jenyffer nascimento (Revista Crioula, 2017)
The article analyzes, from the poem “Reféns da metrópole”, of the collection Terra fértil (2014), by Jenyffer Nascimento, the relationship between lyrical subject and city. It argues that the poem - without hiding the loneliness, depres- sion and deterioration of individual and collective identities in the present tense - develops in relationships among human beings and technological means, exposing the cybercity, in whose spaces disagree and derealize.